Fundamental rights and respect for the difference: fundamentals Constitutional rule of law - De Los Rios Castiblanco, Juan Carlos; De Los Rios Castiblanco, Juan Carlos; De Los Rios Castiblanco, Juan Carlos (Corporación Universitaria Americana, 2022)
In the following lines, rebuilds relevant historical elements that influenced neoconstitutionalism consolidation and discusses some notable foundations and institutions that affect the rights of the first generation, with all its variations and changes of hue, so the recognition and state protection of these fundamental rights and ordering principles of justice, as an order structuring elements adapted to reality. Neoconstitutionalism is ultimately appeal to democratic participation within the boundaries of the fundamental and inalienable rights of the human being, whose reality is driven by a constitutional court which is based on legal instruments such as the control of constitutionality, which ultimately results in the search for respect for difference and the realization of the basic rights of minorities.